Grupo colaborativo como estratégia formativa de articulação da educação infantil com o Ensino Fundamental I - Oliveira, Adriana Beatriz de (2017)
Ação Pedagógica e Avaliação, sob orientação da profa. dra. Laurizete Ferragut Passos The aim of this research was to analyze the possibilities and limits of a collaborative work developed in the implementation process of the Integrative Curriculum of the Childhood from the Municipal System of São Paulo, through narratives of an Early Childhood Education teachers group in partnership with one teacher of the Fundamental Education, from which we sought the articulation between the EMEI and the EMEF in order to give visibility to the Curricular proposal. The group movements during the reflection about their own practices and the local requests emerged as issues for the teaching work. The research had as formulated question: How the reflective movements derived from formative meetings with an Early Childhood Education teachers group contribute with their practices in the implementation process of the Integrative Curriculum of the Childhood from the Municipal System of São Paulo? The theoretical background was based on the National Curricular Guidelines for the Basic Education (MEC, 2013), the Integrative Curriculum of the Childhood of São Paulo (SÃO PAULO, 2015) and the teacher formation in the collaborative work perspective. To deal with this theme authors as Gatti and Barreto (2009), Imbernón (2009), Freire (1996 apud SAUL, 2015), Passos (2016), amog others, were used and allowed the reflection about possible ways which facilitated the understanding of the research problem. The research proposal focused on the Action Special Project (PEA) which takes place in the collective hours of the EMEI where the research was developed. The data were collected during the period of the year 2015 to 2016 using the prose analysis (ANDRÉ, 1983) and the inputs of authors such as Triviños (1987) and Creswell (2010) which helped to expand the scope of data interpretation. The analysis is organized in categories: Dialog between the EMEI and the EMEF and the Mathematics teaching; Articulation of the Integrative Curriculum, and The Collaborative Group composition and the new teaching and trainer apprenticeships. The results revealed the collaborative work as an efficient strategy for the reflection and improvement of the teacher practice since it contributes to the construction of a path that includes the main local requests, giving visibility to the prescribed and the performed Curriculum, through negotiations between the process participants who started to investigate their own actions, thus becoming a community of practice. This research contributes to a new culture of continuous training in the school context, bringing a new meaning for the teaching and the trainer work avoiding the centralization of the formation process and stimulates the valorization of the teacher knowledge, based on its doubts and incertainties, as the fundament of a transformation and reflection process. This process can only be changed if the subjects involved change their disposition in order to learn and to leave the discourse and adopt a thought practice, and also to change from an isolation culture to a collaborative work